Interleaved Boundary Conduction Mode Versus Continous Conduction Mode Magnetic Volume Comparison in Power Converters - Antoszczuk, Pablo Daniel (2016)
Power converters operating in boundary conduction mode (BCM) can benefit from an efficiency increase compared to continuous conduction mode (CCM) based on the soft-switching transitions at turn-on and/or turn-off. However, for a given average inductor current, the RMS current in BCM converters becomes larger than in CCM converters, leading to an increase in conduction losses. Interleaving smaller BCM power converters overcome this drawback by reducing the total ripple current amplitude at the expense of an increase in complexity and in magnetic parts count. Nevertheless, as the magnetic devices are among the largest components in power converters, it is convenient to find the design conditions under which BCM or CCM could yield the smaller net volume. This paper proposes a method to estimate the volume ratio for magnetic parts, between single-phase CCM and multiple interleaved BCM power converters as a function of the number of phases, inductor loss, and switching frequency. The results obtained can be applied to boost, forward, and flyback dc-to-dc topologies.